"n Ondersoek na die siening van wyle professor H P Wolmarans oor kerk en kultuur - Strauss, L. J. (HTS teologiese studies, 2002)
An examination of the views of the late Professor H P Wolmarans on church and cultureThis article endeavors to sketch H P Wolmarans’ view of the interaction between Christian belief and Afrikaner culture in it’s fullest extent. He was lecturer since 1935 to 1959 and dean (1957-1959) of the Faculty Theology (Division A) at the University of Pretoria. His 1938 article “Die godsdiens in ons kultuurstryd” (“Religion in our cultural struggle”) as published in Die Almanak is serves as the point of departure of this review. It is coloured with information about his life and ideas as was obtained from both interviews with family members and former colleagues and articles written by Wolmarans. This article shows that Wolmarans did not practice civil theology. He consistently argued on the basis of Emil Brunner’s dialectical theology that the poltical life of Afrikaners should be built on principles of Scriptures. He did not used the church or theology to serve secular ambitions.